Pengaruh CR, NPM, DAR, dan ITO terhadap Return Saham pada Perusahaan Barang Konsumsi yang Terdaftar di BEI - Karla Karla; Roisantri Marpaung; Ona Lastri Saragih; Novaria Br Tobing; Yois Nelsari Malau (Politeknik Ganesha Medan, 2020)
The purpose of the researchers conducted research to examine how the influence between the current ratio, net profit margin, debt to asset ratio and inventory turnover on stock returns. The population of 50 companies and 92 samples multiplied by four years, using documentation data and purposive sampling techniques with the results of the 2015-2018 IDX financial statements. Hypothesis testing of data is tested using classical assumptions. The coefficient of determination is obtained Adjusted R2 0.081, where the variation of stock return variables described by CR, NPM, DAR, and ITO is 8.1% and other independent variables are 91.9%. The results of the study said that partially CR, DAR, and ITO had no effect but NPM had an effect on stock returns. CR, NPM, DAR, and ITO as a whole have no effect on stock returns.